Analysis of Students' Biology Learning Readiness at SMA Negeri 5 Takalar - Jubrianur, Adriana; Syamsiah, Syamsiah; Patongai, Dian Dwi Putri Ulan Sari (Biology Teaching and Learning, 2024)
This study aims to determine the learning readiness of students at SMA Negeri 5 Takalar in following biology lessons. This type of research is descriptive quantitative research. The population of this study was 498 students, with a sample of 83 students selected using stratified random sampling. The research design used was a survey method with data collection techniques using a learning readiness questionnaire consisting of 30 statements. The data obtained were then analyzed using Microsoft Excel. The results showed that the learning readiness of students at SMA Negeri 5 Takalar was generally in the ready category with an average percentage of 74.03%. The highest readiness indicators were in the very ready category in terms of needs, motives, and goals. Meanwhile, the physical condition, emotional condition, and knowledge were in the ready category. The lowest indicator was in the quite ready category in terms of students' mental condition.